2018
DOI: 10.3390/polym10111203
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxyalkanoate (PHA) Polymer Accumulation and pha Gene Expression in Phenazine (phz-) and Pyrrolnitrin (prn-) Defective Mutants of Pseudomonas chlororaphis PA23

Abstract: Pseudomonas chlororaphis PA23 was isolated from the rhizosphere of soybeans and identified as a biocontrol bacterium against Sclerotinia sclerotiorum, a fungal plant pathogen. This bacterium produces a number of secondary metabolites, including phenazine-1-carboxylic acid, 2-hydroxyphenazine, pyrrolnitrin (PRN), hydrogen cyanide, proteases, lipases and siderophores. It also synthesizes and accumulates polyhydroxyalkanoate (PHA) polymers as carbon and energy storage compounds under nutrient-limited conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…The PCR results suggested that ST-TJ4 contains genes for the biosynthesis of PCA and PRN. Phenazine type of antibiotics, such as PCA, are particularly active against oomycetes [43,44]. Park et al [45] demonstrated that PRN produced by P. chlororaphis O6 plays a pivotal role in inhibiting Phytophthora infestans, which causes tomato late blight disease.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR results suggested that ST-TJ4 contains genes for the biosynthesis of PCA and PRN. Phenazine type of antibiotics, such as PCA, are particularly active against oomycetes [43,44]. Park et al [45] demonstrated that PRN produced by P. chlororaphis O6 plays a pivotal role in inhibiting Phytophthora infestans, which causes tomato late blight disease.…”
Section: Discussionmentioning
confidence: 99%
“…P. chlororaphis PA23-63-1 is able to grow in RMM containing different vegetable oils as a sole carbon source and produce PHAs (Sharma et al 2018). The identity of this strain was confirmed on the basis of genome sequencing (Loewen et al 2014).…”
Section: Bacteria Degrading Phasmentioning
confidence: 87%
“…Bacterial cultures, media and growth conditions P. chlororaphis PA23 is a plant growth promoting bacterium isolated from the rhizosphere of soybeans, capable of suppressing growth of the fungal pathogen Sclerotinia sclerotiorum due to its ability to synthesize and secrete two anti-fungal compounds, phenazine and pyrrolnitrin (Fernando et al 2007;Savchuk and Fernando, 2004). P. chlororaphis PA23-63-1 is a mutant strain of P. chlororaphis PA23 that is defective in phenazine and pyrrolnitrin production, and is also able to synthesize mcl-PHAs (Sharma et al 2018). P. chlororaphis PA23-63-1 was kindly provided by All bacteria used in this study were grown and purified on LB plates incubated at 30 o C for 24 hours (h).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ralstonia eutropha, one of the most well-known PHA-producing bacteria, can accumulate PHA at up to 80% of its dry cell weight [ 24 , 25 , 26 ]. However, the wild-type strain can synthesize only the P(3HB) monomer.…”
Section: Introductionmentioning
confidence: 99%